A physical model of the estimation of the chlorophill a in the Peruvian sea using MODIS images - Quezada García, M. G. (2011)
The chlorophyll a is an indicator of the plankton biomass for track flows, jets and oceanographic feathers and is used as an entry for primary production models. The chlorophyll a in the Peruvian sea surface can be measured by means of satellite remote sensing in the visible spectral range from 0.4 to 0.7 μm. This work aims to develop a physical model for the estimation of chlorophyll a concentration from the MODIS images in the Peruvian sea.